Two Decades Later: A Bibliographic Revision of Menegazzia in Chile with New Identification Key and Phylogenetic Perspectives - David Alors (Diversity, 2025)
This study presents a bibliographic review of the genus Menegazzia in Chile, the first in over two decades, updating new records, the taxonomic placement of the genus, and the synonymization of species. Up to twenty species have been cited in the country, considering that M. albida, M. hollermayeri, and M. norstictca are synonyms of the valid species M. wilsonii, M. dispora, and M sanguinascens. A fully revised dichotomous key and color photographs are included to facilitate accurate identification, especially given the genus’s morphological convergence and sparse reproductive structures. For the first time, the divergence times of Menegazzia lineages are discussed in relation to major Southern Hemisphere geologic events, suggesting a dispersal-driven distribution with a crown age of approximately 21.2 Ma. This review consolidates fragmented data, integrates recent molecular findings, and emphasizes the genus’s value as an ecological and biogeographic indicator in Chilean temperate forests.